Autologous hematopoietic stem cell transplantation improves long-term survival-data from a national registry - Blank, Norbert; Schmalzing, Marc; Moinzadeh, Pia; Oberste, Max; Siegert, Elise; Mueller-Ladner, Ulf; Riemekasten, Gabriela; Guenther, Claudia; Koetter, Ina; Zeidler, Gabriele; Pfeiffer, Christiane; Juche, Aaron; et al. (Arthritis Research & Therapy, 2022)
Background Current recommendations on the management of systemic sclerosis (SSc) suggest that autologous hematopoietic stem cell therapy (HSCT) can be a rescue therapy for patients with rapidly progressive SSc. Objectives To assess the safety and efficacy of HSCT for patients with SSc and to compare these with non-HSCT patients in a control cohort with adjusted risk factors. Methods A retrospective analysis of data from the multicentric German network for systemic scleroderma (DNSS) with 5000 patients with SSc. Control groups consisted of all patients with diffuse cutaneous (dc)-SSc (group A) and an adjusted high-risk cohort of male patients with Scl70-positive dc-SSc (group B). Results Eighty SSc patients received an HSCT 4.1 +/- 4.8 years after SSc diagnosis. Among them, 86.3% had dc-SSc, 43.5% were males, and 71.3% were positive for Scl70 antibodies. The control group A (n=1513) showed a significant underrepresentation of these risk factors for mortality. When the survival of the control group B (n=240) was compared with the HSCT group, a lower mortality of the latter was observed instead. Within 5 years after HSCT, we observed an improvement of the mRSS from 17.6 +/- 11.5 to 11.0 +/- 8.5 (p=0.001) and a stabilization of the DLCO. We did not see differences in transplant-related mortality between patients who received HSCT within 3 years after SSc diagnosis or later. Conclusion Our analysis of real-life data show that the distribution of risk factors for mortality is critical when HSCT cohorts are compared with non-HSCT control groups.
CRIS-Team WoS Importer:2022-12-02